Cryptanalysis of Application of Laplace Transform for Cryptography - Gencoglu, Muharrem Tuncay (E D P Sciences, 2017)
Although Laplace Transform is a good application field in the design of cryptosystems, many cryptographic algorithm proposals become unsatisfactory for secure communication. In this cryptanalysis study, one of the significant disadvantages of the proposed algorithm is performed with only statistical test of security analysis. In this study, Explaining what should be considered when performing security analysis of Laplace Transform based encryption systems and using basic mathematical rules, password has broken without knowing secret key. Under the skin; This study is a refutation for the article titled Application of Laplace Transform for Cryptography written by Hiwerakar[3].
2nd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 20-22, 2017 -- Istanbul, TURKEY
Keywords: Laplace Transform; Cryptography; Cryptanalysis; A general attack scenario